Pharmacoeconomical assessment of сerebrolysin in the treatment of the acute disturbances of cerebral circulation - A. Yu. Kulikov; L. A. Komarov (IRBIS LLC, 2015)
Abstract: the acute disturbances of cerebral circulation incidence accounts for nearly 70-80% of all such diseases in population, while this annual rate in Russian health care is about 2,19 cases on 1000 individuals. Pharmacoeconomic evaluation of this pathology contributes to the improvement of approaches to treatment policy of this group of patients. We performed cost-effectiveness analysis on the basis of сerebrolysin in acute disturbances of cerebral circulation treatment on the top of standard therapy compares with only standard therapy. As a result treatment with сerebrolysin on the top compared with standard therapy is characterized as dominant according to cost-effectiveness analysis data. Finally, the results of budget impact analysis illustrate that including сerebrolysin into the standard therapy of acute disturbances of cerebral circulation in comparison with only standard therapy has potential to reduce Russian healthcare system total costs for acute disturbances of cerebral circulation treatment.